Analisis Sistem Informasi Akuntansi Proses Konfirmasi Uang Muka Dinas Operasional Pada PT Semen Indonesia (Persero) Tbk - Jannata, Putrila Maya; Vendy, Vicky (Jurusan Akuntansi Politeknik Negeri Padang, 2024)
This research aims to analyze the effectiveness and efficiency of the accounting information system for the down payment for the operational services process using Macro VBA. This research uses a descriptive qualitative research method. The study was conducted at PT Semen Indonesia (Persero) Tbk. Involving four informants in April 2024. The primary data used is gathered on-site through observation, interviews, and documentation. The results obtained from this research include a description of the flowchart and procedures for confirming operational advances. The operational advance confirmation system using Macro VBA has been running according to the guidelines. The process involves flowcharts of the divisions involved. PT Semen Indonesia (Persero) Tbk uses Macro VBA to improve work efficiency and effectivity in the operational advance confirmation process. The implementation of Macro VBA in the advance confirmation process has proven to increase work efficiency and effectivity by speeding up the data processing and reminder-sending processes. Additionally, the use of Macro VBA successfully reduced the need for manual labor, allowing employees to allocate their time to other tasks.